Donor specific transplant tolerance is dependent on complement receptors. (20th November 2012) - Bartel, Gregor; Brown, Kathryn; Phillips, Richards; Peng, Qi; Zhou, Wuding; Sacks, Steven H.; Wong, Wilson
Summary The complement system has recently been described as a crucial component for transplant tolerance induction, but the underlying mechanisms are poorly understood. Using a rodent model of donor lymphocyte infusion‐induced male histocompatibility antigen‐specific transplant tolerance, we demonstrate that tolerance induction is dependent on the complement receptors decay accelerating factor, complement receptor 3, and complement component 3a receptor (C3aR). Furthermore, we have provided evidence that complement dependent tolerance is mediated through C3aR on infused donor splenocytes and on recipient cells. Ex vivo studies showed that C3aR deficiency leads to an imbalance between T regulatory and T effector cells. Increased numbers of antigen‐specific CD8+ cells in the blood and less T regulatory cells, with reduced suppressive function, in the spleen and in the skin grafts were detected in C3aR deficient compared to wild type mice. This imbalance might be explained by the requirement of complement for dendritic cells to generate T regulatory cells effectively. Our experiments suggest that multiple complement receptors play an important role in transplant tolerance induction providing new insights into the mechanisms of complement dependent tolerance.